Mekanisme Pasar dan Regulasi Harga: Telaah atas Pemikiran Ibnu Taimiyah - Junia Farma (Universitas Muhammadiyah Magelang, 2018)
Islam has an essential position in the market mechanism. But, it needs some requirements to be perfect in the market. However, in reality, market distortions have occurred, it will make the injustice price determination. Rising price as a result of injustice or malpractices on the part of sellers leading to imperfection in the market. One of the Islamic scholar, Ibnu Taimiyah, explained that price is determined by the power of demand and supply. But, in the case of a rising price caused by injustice market mechanism, government intervention is needed to determined justice price. Therefore, Ibnu Taimiyah thinking about price regulation not just only give a deep analysis of what has occurred in that time, but it also can be used nowadays and reasonable to apply in the society